2018
DOI: 10.2355/isijinternational.isijint-2018-077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cementite Dispersion on Void Formation Process in Spheroidize-Annealed Steels

Abstract: The effect of cementite dispersion on ductile fracture was investigated by comparing void formations in different spheroidize-annealed steels. Two types of steels with different grain sizes and interparticle distances were used. Tensile tests of plate specimens were performed in longitudinal direction along the rolling direction. After the tensile tests, the fractured specimens were cut in the middle along the width. The cross sections near the fractured surface were observed using a scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This criterion was determined to distinguish between voids initiated after punching and those initiated before punching. 8) The void number density N V was calculated using Eq. (1), and used as an index to represent void initiation,…”
Section: Evaluation Of Voids Near Punched Surface Aftermentioning
confidence: 99%
See 1 more Smart Citation
“…This criterion was determined to distinguish between voids initiated after punching and those initiated before punching. 8) The void number density N V was calculated using Eq. (1), and used as an index to represent void initiation,…”
Section: Evaluation Of Voids Near Punched Surface Aftermentioning
confidence: 99%
“…6) These previous studies compared voids near the fracture surface of steel sheets with the hole-expansion ratio of another sample in the same steel sheet. In contrast, excellent stretch-flange formability of spheroidized, annealed, medium-carbon steel has been determined, 7) and the effects of spheroidized cementite dispersion on void initiation during tensile testing 8) and punching 9) have been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Gammage et al [ 18 ] observed that inhomogeneity in precipitate distributions leads to local stress concentration, which is a key factor in interfacial heterogeneous fracture initiation. Maeda et al [ 19 ] confirmed that the strain around carbide particles decreases as carbide size decreases in steel sheets. The results of those studies indicate the necessity of a new type of shape factor, by which the physical stress properties can be signature from the geometry shape.…”
Section: Introductionmentioning
confidence: 99%